Diabetes: The quest for basal normoglycaemia. - Holman, R; Turner, R (1977)
Diabetes is an endocrine deficiency disease, a logical treatment of which is hormone replacement therapy. Many patients who are thought to be controlled by diet alone continue to have high plasma-glucose levels. As the rise in the basal plasma glucose concentration is the predominant glucose abnormality of diabetes, treatment should be aimed primarily at producing basal normoglycaemia. 18 mild, maturity onset diabetics have been treated with a basal insulin supplement provided by single daily injections of insulin zinc suspension (crystalline) 'Ultralente'. Overnight basal normoglycaemia has been obtained with markedly reduced plasma-glucose levels during the day. Plama-triglyceride levels have become normal in most patients. The required insulin dose need not be determined empirically, but can be calculated from the basal plasma-glucose level and the degree of obesity. There is minimum risk of hypoglycaemia, and rigid dietary restriction is unnecessary. As mild diabetics are prone to complications, treatment with basal insulin supplements may be beneficial when diet alone fails to produce basal normoglycaemia.